Improving Student's Understanding About Animal Metamorphosis through Ecoterm Media for Deaf Student - Putri, Lamina Amalia; Susetyo, Budi; Homdijah, Oom Sitti; Hernawati, Tati; Gunawan, Dudi (Jurnal Pendidikan Matematika dan Sains, 2025)
This study aims to improve the understanding of deaf students in class VII Junior High School at SLBN Cicendo on animal metamorphosis material through ecoterm media. The method used was classroom action research with five learners as subjects. The research instruments included interview guidelines, observations, and written objective test adapted to the independent phase D curriculum on animal metamorphosis material. In the pre-cycle stage, learning using conventional media (videos) only achieved classical completeness of 20%. After the application of ecoterm media, the completeness increased to 40% in cycle I and 100% in cycle II. The written test results also showed a gradual increase. The ecoterm media proved to be effective because it provided a concrete learning experience that involved various sensory modalities, making it easier to understand abstract concepts such as animal metamorphosis. This study concludes that ecoterm media can significantly improve deaf learners' understanding of animal metamorphosis learning materials, helping them achieve more optimal learning outcomes.